Delayed Tooth Replantation after Traumatic Avulsion: A Case Report - Khalilak, Zohreh; Shikholislami, Mahshid; Mohajeri, Ladan (Iranian Endodontic Journal, 2009)
Avulsion is a serious injury which causes damage to dental and supportive tissues, ranging from 1-16 % among dental injuries and it mostly occurs in maxillary incisors. This report presents a case of replantation of a traumatically avulsed central incisor. The left central incisor of an 8 year-old boy with open apex was avulsed and was left in unclean and dry conditions. Tooth was replaced after 270 min and splinted. After 24 hours, tooth was treated endodontically. The calcium hydroxide paste was applied as intracanal medicament. After one year the calcium hydroxide was not replaced and was maintained in the canal, permanently. The tooth followed for 5 years. During follow up, the tooth kept stable. However, the resulted dent alveolar ankylosis prevented growth of the alveolar process. Spite of the fact that in children, replacement resorption leads to the loss of ankylosed teeth within 1-5 years; this tooth has remained in a stable, infra-position for 5 year and in functional position after coronal restoration. However, in such cases other treatments such as decoronation should be considered.